Abalos + Sentkiewicz essays on thermodynamics, architecture and beauty. - Abalos, Iñaki; Snetkiewicz, Renata (Actar D, 2015)
A compendium of essays and projects, that creates a projective document, able to set up new scenarios for the Architecture of the next decade.